KULOCS: unified locating service for efficient development of location-based applications. Issue 1 (4th April 2016) - Takatsuka, Hiroki; Tokunaga, Seiki; Saiki, Sachio; Matsumoto, Shinsuke; Nakamura, Masahide
Abstract : Purpose: The purpose of this paper is to develop a facade for seamlessly using locating services and enabling easy development of an application with indoor and outdoor location information without being aware of the difference of individual services. To achieve this purpose, in this paper, a unified locating service, called KULOCS ( Kobe-University Unified LOCating Service ), which horizontally integrates the heterogeneous locating services, is proposed. Design/methodology/approach: By focusing on technology-independent elements [when], [where] and [who] in location queries, KULOCS integrates data and operations of the existing locating services. In the data integration, a method where the time representation, the locations and the namespace are consolidated by the Unix time, the location labels and the alias table, respectively, is proposed. Based on the possible combinations of the three elements, an application-neutral application programming interface (API) for the operation integration is derived. Findings: Using KULOCS, various practical services are enabled. In addition, the experimental evaluation shows the practical feasibility by comparing cases with or without KULOCS. The result shows that KULOCS reduces the effort of application development, especially when the number of locating services becomes large. Originality/value: KULOCS works as a seamless facade with the underlying locating services, the users and applications consume location information easily and efficiently, without knowing concrete services actually locating target objects.